Bioinspired synthesis of SnO crosses as backbone in artificial sponges. (10th June 2019) - Jahnke, Timotheus; Kilper, Stefan; Knöller, Andrea; Brümmer, Franz; Widenmeyer, Marc; Rothenstein, Dirk; Burghard, Zaklina; Bill, Joachim
Abstract : The distinct electronic properties, including p-type semiconducting and a wide optical band gap, renders SnO suitable for applications such as microelectronic devices, gas sensors and electrodes. However, the synthesis of SnO is rather challenging due to the instability of the oxide, which is usually obtained as a by-product of SnO2 fabrication. In this work, we developed a bioinspired synthesis, based on a hydrothermal approach, for the direct production of SnO nanoparticles. The amount of mineralizer, inducing the precipitation, was identified, which supports a template-free formation of the nanosized SnO particles at low temperature and mild chemical conditions. Moreover, the SnO nanoparticles exhibit a shape of unique three-dimensional crosses similar to the calcite crosses present in the calcareous sponges. We demonstrated that SnO crosses are evenly distributed and embedded in an organic scaffold by an ice-templating approach, in this way closely mimicking the structure of calcareous sponges. Such scaffolds, reinforced by an active material, here SnO, could be used as filters, sensors or electrodes, where a high surface area and good accessibility are essential. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology (part 2)'.